Impact of analgesic regimen on patient outcome following subarachnoid hemorrhage: positive adjuvant effects of metamizole - Solar, Peter; Joukal, Marek; Silar, Cenek; Jancalek, Radim (British journal of neurosurgery, 2024)
INTRODUCTION: Various analgesics are used to control intense headaches in patients following subarachnoid hemorrhage. In addition to pain control, it has been shown that some analgesics can affect various pathophysiological cascades. Therefore, we devised a study to assess whether the use of metamizole has a significant impact on the development of ischemic complications, hydrocephalus, and the overall outcome in patients following aneurysmal subarachnoid hemorrhage in the context of the other non-opioids and opioids effects. METHODS: In our retrospective, single-center cohort study, we enrolled 192 patients diagnosed with subarachnoid hemorrhage. We recorded their initial clinical status, comorbidities, and the daily dosage of analgesics over 14 days of hospitalization after the onset of subarachnoid hemorrhage. Using univariate and subsequent multivariate logistic regression analysis, we assessed the influence of various factors, including analgesics, on the development of delayed cerebral ischemia and hydrocephalus, as well as on 2-week and 6-month outcomes. RESULTS: Although the administration of non-opioids, in general, had no effect on the development of delayed cerebral ischemia or hydrocephalus, the use of metamizole as the main analgesic was associated with a significantly lower chance of poor outcome at both 2-weeks and 6-months, as well as the development of delayed cerebral ischemia. As opioids were indicated primarily for analgosedation in mechanically ventilated patients with poor clinical status, their usage was associated with a significantly higher chance of poor outcome, delayed cerebral ischemia, and hydrocephalus. CONCLUSION: Our results suggest that the prescription of metamizole may be associated with better outcomes and a lower chance of delayed cerebral ischemia development in patients after subarachnoid hemorrhage. Considering the retrospective nature of our study and the limited worldwide availability of metamizole due to its prohibition in some countries, our results do not demonstrate a clear benefit but rather justify the need for subsequent prospective studies.
Keywords: dospělí; hydrocefalus; Dipyrone; antiflogistika nesteroidní; Female; Adult; Analgesics; výsledek terapie; ženské pohlaví; metamizol; lidé; hydrocephalus; Treatment Outcome; ischemie mozku; subarachnoidální krvácení; Anti-Inflammatory Agents, Non-Steroidal; Hydrocephalus; retrospektivní studie; analgesic drugs; Male; Aged; analgetika; Brain Ischemia; metamizole; lidé středního věku; Subarachnoid Hemorrhage; senioři; mužské pohlaví; Subarachnoid hemorrhage; patient outcome; Retrospective Studies; Middle Aged; Humans